2001
DOI: 10.1002/jtra.1050
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of post‐receptor insulin signaling by trivalent chromium in hepatoma cells is associated with differential inhibition of specific protein‐tyrosine phosphatases

Abstract: Various molecular forms of chromium have been implicated in the regulation of glucose metabolism, and chromium deficiency can be associated with insulin resistance and impaired glucose tolerance. Protein-tyrosine phosphatases (PTPases), which negatively regulate signaling through the insulin receptor, are potential targets of chromium action, since this transition metal may inhibit catalysis at the thiol-dependent active sites of these enzymes. Treatment of cultured rat hepatoma cells with 0.1 mM CrCl 3 for 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 37 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…However, the mechanism by which chromium enhances insulin-stimulated Akt phosphorylation is unclear. One potential explanation could be the inhibition of the enzyme phosphotyrosine phosphatase (PTP-1B) by chromium, which is a known negative regulator of insulin signaling [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism by which chromium enhances insulin-stimulated Akt phosphorylation is unclear. One potential explanation could be the inhibition of the enzyme phosphotyrosine phosphatase (PTP-1B) by chromium, which is a known negative regulator of insulin signaling [27].…”
Section: Discussionmentioning
confidence: 99%
“…Vincent's group found that LMWCr (complete with Cr) enhanced phosphatase activity (although not necessarily PTP-1B) in adipocyte membranes but did see a significant reduction in activity with Cr in PTP-1B in rat hepatoma cells. 81,82 In addition, Wang et al saw reductions in both expression and activity of PTP-1B in the skeletal muscle of obese rats treated with Cr picolinate. 17 Insulin Receptor Substrate 1 (IRS-1) can also be phosphorylated on a specific serine residue which prevents it from activating PI3K so reducing insulin signaling.…”
Section: Mechanism Of Actionmentioning
confidence: 99%